A new approach to fabricate MgO-C refractories with high thermal shock resistance by adding artificial graphite. Issue 4 (April 2018) - Zhu, Tianbin; Li, Yawei; Sang, Shaobai; Xie, Zhipeng
Abstract: To lower the carbon content but to exhibit a better thermal shock resistance with MgO-C refractories containing 14 wt% flaky graphite, a new approach, based on the addition of artificial graphite, is reported for enhancing the thermal shock resistance of such refractories with 10 wt% graphite in the present work. The addition of artificial graphite (not more than 2 wt%) has a slight influence on the flexural strength of the specimens, but apparently enhances their thermal shock resistance. In particular, the specimen containing 2 wt% artificial graphite has a higher flexural strength after thermal shocks and a relatively closer residual strength ratio as compared to the reference specimen with 14 wt% flaky graphite, as it is related with the formation of more AlN reinforced phases, decreased coefficient of thermal expansion as well as increased work of fracture.